Isotope fractionation during root water uptake by Acacia caven is enhanced by arbuscular mycorrhizas - Poca, María (2019)
Aim: A growing number of studies show a discrepancy between the isotopic composition of xylem water and plant water sources. We tested the effect of arbuscular mycorrhizal fungi (AMF) on the isotopic composition of Acacia caven xylem water. As the most common plant-fungal association, AMF might explain this isotopic mismatch. Methods: Seedlings were grown with and without AMF and irrigated with the same water. After 120 days, stem and soil samples were collected and following cryogenic distillation, H and O isotopic composition of xylem and soil water, as well as irrigation water, was measured. Results: Xylem water of non-mycorrhizal seedlings was significantly depleted in 2H compared to soil water (differences up to −15.6‰). When AMF were present, the depletion was significantly higher and appeared for both H and O (differences up to −24.6‰ for δ2H and − 2.9‰ for δ18O between soil and xylem water). Conclusions: Results suggest that isotopic fractionation occurred during water uptake in this xerophytic species. To explain this, we propose an aquaporin-driven mechanism mediating water transport via transmembrane passage. Furthermore, we show for the first time, that AMF enhance the observed discrimination against heavy isotopes, probably by enforcing water passage through aquaporins. Given their ubiquity, AMF could question the fractionation-free assumption during root water uptake.